Peran Gizi dalam Pencegahan Stunting di Indonesia - Chindy Amir; Fatma Syukrina (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2025)
Stunting, defined as a growth disorder in children under five caused by chronic malnutrition, remains a significant public health challenge in Indonesia (Bahrun & Wildan, 2022). The high prevalence of stunting impacts children’s physical growth, cognitive development, and future quality of life (Sutarto et al., 2018). This study aims to provide an overview of the role of nutrition in preventing stunting, with a focus on supplementary feeding (PMT) as an effective nutritional intervention. The method employed involved providing guidance to families with stunted infants on providing supplementary food appropriate to the child’s nutritional needs. The guidance activities included education on the importance of balanced nutrition, providing sample menus for supplementary feeding based on local food ingredients, and monitoring changes in feeding practices for the children. The main results of the activities showed an increase in mothers’ or caregivers’ knowledge regarding nutrition and stunting, positive changes in supplementary feeding practices, and improvements in children’s health and growth and development. The conclusion of this study is that continuous mentoring is a crucial strategy in supporting the accelerated reduction of stunting in Indonesia